The application of orthogonal array analysis to the screen printing process - Eifion Jewell (1995 European Taguchi Methods and QFD Symposium, 1995)
This paper outlines the development and results of a comprehensive experimental programme to investigate the effect of the primary screen printing parameters on the print quality. The selection of the parameters to be included in the experiments was based on both experience and discussions with industry. Three key areas were identified which were thought to have a substantial effect on the print quality; these were mesh characteristics, squeegee characteristics and ink rheology. Since the investigations found a number of parameters which may have an effect on the quality of the screen process a full factorial experiment was deemed impractical and thus it was decided to use orthogonal array analysis. By engineering design and astute choice of variables, an L18 orthogonal array for the print machine parameters consisting of mesh tension, mesh structure, mesh ruling, a squeegee pressure and edge hardness parameter, squeegee angle and ink characteristics was developed. A test form was designed which facilitated the measuring of image distortion and tonal reproduction Five copies were analyzed from each experiment using spectrophotometry. Control conditions were specified which ensured minimum variation between successive experiments by controlling the ink temperature, room temperature and screen ink film thickness. It was found that 7 of the 8 parameters chosen effect the quality of the printed image and that the experiment had been a success. Recommendations for further investigations are made.